Retraction notice to “Immunomodulatory effects of β-defensin 2 on tumor associated macrophages induced antitumor function in breast cancer” [Adv. Cancer Biol. – Metastasis 7 (2023) 100102] - Sonam Agarwal; Anita Chauhan; Pramod Kumar Gautam (Advances in Cancer Biology - Metastasis)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal).This article has been retracted at the request of the Editor-in-Chief.Concern was raised about validity and reliability of the data, experimental procedures, data analysis methods and consequently the result of the article.The Editors requested the corresponding author to repeat the experiments at least three times and provide the raw data and standard deviations for the statistically evaluated results. However, the authors did not follow the Editors' recommendations and were unable to provide adequate response for comment. The overall validity of the results could not be confirmed. Therefore, the Editor-in-Chief decided to retract the article.